Penerapan Manajemen Risiko untuk Meningkatkan Keberlanjutan Platform Layanan Konsinyasi di Indonesia - Lubis, Rima Octaviani; Indradewa , Rhian; Abadi, Ferryal; Kustiawan, Unggul (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
Risks are inherent in every industry, potentially occurring and difficult to avoid, but they can be effectively managed and controlled. Risks in the dropshipping platform industry include intense competition, regulatory changes, currency fluctuations, and the potential for fraud or damage to goods. This research aims to evaluate the effectiveness of risk management implementation within the TITIP organization The research method used is a descriptive method. Identification, analysis, and evaluation of the risks faced. The location of this research is at the TITIP business. The results of the risk analysis reveal a diverse range of risks impacting various aspects of operations, marketing, human resources, and finance. The research concludes by highlighting the crucial importance of communication and consultation, regular risk assessments, and the proper implementation of mitigation measures. Recommendations suggest that the organization should continuously enhance employee awareness regarding risk management and optimize the allocation of resources for risk management.